The Qur’an as a transformation factor: A survey on Reading vs Understanding the Qur’an among the students of the International Islamic University Malaysia - Sulaiman, Kabuye Uthman (2012)
The Qur’an is the basis of Islam and an intrinsic part of a Muslim life. It is the strong rope that connects Muslims to their Lord, Allah, the Straight Path (al-Sirat al-Mustaqim)leading them to everlasting bliss and the backbone of their success in both existences, i.e. al-Dunya and al-Akhirah (here and hereafter). The purpose of this paper is to explore how the students of the International Islamic University Malaysia read the Qur’an. It is undeniable that recitation of the Qur’an is an activity in which Muslims engage from childhood to death. No day passes without the Qur’an being read. Despite this, however, it is unfortunate that not many Muslims understand what they read from the Qur’an! The researcher contends that understanding the Qur’an is essential if Muslims are to uplift themselves from the current state of moral, spiritual, political and economic decline; that Muslims would have been the leaders of the world today had they been able to continue dealing with the Qur’an the way it was dealt with by the Prophet’s companions and their immediate successors; and that understanding the Qur’an is the greatest challenge facing Muslims today. Key Words: Qur’an, reading, understanding, reflection, transformation.